The ups and downs of miR-205: Identifying the roles of miR-205 in mammary gland development and breast cancer - Greene, Stephanie B.; Herschkowitz, Jason I.; Rosen, Jeffrey M. (RNA biology, 2010)
Recent studies have demonstrated that miR-205 has a role in both normal development and cancer, however conflicting reports on its function illustrate the complexity of its regulation and targets. Additionally, miR-205 was found to be highly expressed in stem cell-enriched populations from the mouse mammary gland, and thus may play a function in normal mammary stem cell maintenance. The role that miR-205 plays in tumor formation and metastasis is likely context-dependent as reports have indicated that it may function as either a tumor suppressor or an oncogene. The role that miR-205 plays in directing stem cell fate is still unknown.